Vijayamaṅkalam - Murukarāj, Ā.; Śrītar, Ti. Śrī., 1955-; Tamil Nadu (India). Department of Archaeology (Ceṉṉai : Tamiḻnāṭu Aracu Tolliyal Tuṟai, 2009)
Study on Hindu temples in Vijayamangalam, town in Tamil Nadu; socio-historical perspective.
Includes bibliographical references (pages 122-123).
Mode of access: Internet.
In Tamil.
Keywords: Hindu temples -- India -- Vijayamangalam -- History; Vijayamangalam (India) -- History; Vijayamangalam (India) -- Religion